TNF signalling drives expansion of bone marrow CD4+ T cells responsible for HSC exhaustion in experimental visceral leishmaniasis. - Ana Isabel Pinto; Ana Isabel Pinto; Najmeeyah Brown; Olivier Preham; Johannes S P Doehl; Helen Ashwin; Paul M Kaye (PLoS Pathogens)
Visceral leishmaniasis is associated with significant changes in hematological function but the mechanisms underlying these changes are largely unknown. In contrast to naïve mice, where most long-term hematopoietic stem cells (LT-HSCs; LSK CD150+ CD34- CD48- cells) in bone marrow (BM) are quiescent, we found that during Leishmania donovani infection most LT-HSCs had entered cell cycle. Loss of quiescence correlated with a reduced self-renewal capacity and functional exhaustion, as measured by serial transfer. Quiescent LT-HSCs were maintained in infected RAG2 KO mice, but lost following adoptive transfer of IFNγ-sufficient but not IFNγ-deficient CD4+ T cells. Using mixed BM chimeras, we established that IFNγ and TNF signalling pathways converge at the level of CD4+ T cells. Critically, intrinsic TNF signalling is required for the expansion and/or differentiation of pathogenic IFNγ+CD4+ T cells that promote the irreversible loss of BM function. These findings provide new insights into the pathogenic potential of CD4+ T cells that target hematopoietic function in leishmaniasis and perhaps other infectious diseases where TNF expression and BM dysfunction also occur simultaneously.